Problems Of Students' Arabic Translation in Tarjamah Course in The Islamic Religious Education Study Program Of Stai Ma'had Aly Al-Hikam Malang.: Problematika Penerjemahan Bahasa Arab Mahasiswa pada Mata Kuliah Tarjamah - Imam Athoir Rokhman (STAI Nurul Huda Kapongan Situbondo, 2023)
Many Islamic Religious Education students of STAI Ma'had Aly Al-Hikam experience difficulties in translating texts from Arabic to Indonesian, as reflected in their translations. This is a natural thing to happen to students and novice translators due to the different characteristics between the source and target languages. However, if this problem is not overcome, it can hinder students' understanding of Arabic literature. The purpose of this study is to identify the problems that arise when translating. This research uses quantitative approach with survey method. The research subjects were second-semester students who were taking the tarjamah course. The researcher used a questionnaire to collect data and analyzed it using descriptive analysis. The result of this study is that the problems in translating Arabic texts for students of the Islamic Religious Education study program at STAI Ma'had Aly Al-Hikam Malang are influenced by two aspects, namely linguistic and non-linguistic aspects.